Pembuatan Pupuk Organik Cair dari Limbah Kulit Bawang Merah - Pakpahan, Enni Halimatussa’diyah; Silvia, Cindy; Ananda, Uci Fitri (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The production of shallots has been increasing among the community from year to year. The large amount of shallot skin waste can cause new problems that affect environmental pollution if not handled immediately. The purpose of this research is to provide knowledge about making liquid organic fertilizer from shallot skin waste. Compounds found in shallot skin contribute to soil fertility and have a positive impact on plants. The research methodology used is an experimental approach by applying a method of making liquid organic fertilizer from leftover shallot skin. The research findings show that leftover shallot skin can be used as liquid organic fertilizer that has many benefits in plant growth. In line with previous findings, chili plants can utilize liquid organic fertilizer made from shallot skin application to grow faster. In addition to chili plants, liquid organic fertilizer can also help the growth of okra, mustard greens, spinach, tomatoes, and ornamental plants.